2007
DOI: 10.1007/s10562-007-9149-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Reformer Trap by Use of Transition Metal Oxide-Incorporated Beta Zeolites

Abstract: The concept of a hydrocarbon reformer trap is proposed as a novel technology for cleaning up automobile emissions. Zeolite beta with/without metal species such as iron, manganese, or cobalt is synthesized through a solid phase transformation of mesoporous (metallo)aluminosilicate MCM-41 along with tetraethylammonium cations for structure direction to zeolite beta. The microporosity of zeolite functions as a hydrocarbon trap, and the metal species inside the pores provide a reforming site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Thus, it was suggested that Fe‐loaded zeolites can catalyze toluene oxidation. The concept of the proposed HC reformer trap is confirmed here in further detail. Fe‐containing zeolites are known to be effective catalysts for various reactions, such as the selective catalytic reduction of nitrogen oxides with hydrocarbons or ammonia, the hydroxylation of benzene or methane with N 2 O, and the direct decomposition of N 2 O .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it was suggested that Fe‐loaded zeolites can catalyze toluene oxidation. The concept of the proposed HC reformer trap is confirmed here in further detail. Fe‐containing zeolites are known to be effective catalysts for various reactions, such as the selective catalytic reduction of nitrogen oxides with hydrocarbons or ammonia, the hydroxylation of benzene or methane with N 2 O, and the direct decomposition of N 2 O .…”
Section: Resultsmentioning
confidence: 99%
“…Toluene‐TPD was used to evaluate the zeolites as a HC trap . A mixture of 20 mg of zeolite with 100 mg of silicon carbide was placed in a 5 mm inner‐diameter glass tube and pretreated at 390 °C for 1 h in a He stream with or without O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very few papers have reported it so far. Ogura et al [18] prepared Mn-loaded Al-b zeolite through the solid phase transformation of Mn-containing mesoporous silica MCM-41, and used it as an effective hydrocarbon reformer trap for cleaning up automobile emissions, but they did not characterize the state of manganese in zeolite structure. In this study, the incorporation of manganese into the framework of b zeolite is achieved by a direct hydrothermal synthesis without adding any assistant agents, which is evidenced by XRD, UV-vis, and inductively coupling plasma (ICP).…”
Section: Introductionmentioning
confidence: 99%